The ideal patient specific implant. Part II: An eight step checklist for maxillary class I, II Brown defects - Sanjay Kumar Roy Chowdhury; Karan Padha; Sneha Singh; Pradeep Yadav; Ravi Prajapati (Elsevier, 2023)
Patient specific implants (PSI) though considered the next frontier in Maxillofacial Reconstruction, the gold standard for Brown I, II maxillary defects still remains autogenous reconstruction. The authors in their previous papers have standardised the design of Patient Specific Implants for Brown I, II mandibular defects. In this paper they attempt to standardise the design of PSI for Brown I,II maxillary defects using a scientifically optimised design which has passed through a stringent set of parameters. They aim to address the complications like wound dehiscence, poor dimensional accuracy and unoptimised biomechanics due to lack of standardisation thus impeding it's widespread acceptance among the scientific community. This study presents an eight step checklist to be followed for designing of an ideal standardised patient specific implant and can serve as a go-to guide for the operating and designing team.